Role of CXCR1 and Interleukin-8 in Methamphetamine-Induced Neuronal Apoptosis - Du, Si-Hao; Zhang, Wei; Yue, Xia; Luo, Xiao-Qing; Tan, Xiao-Hui; Liu, Chao; Qiao, Dong-Fang; Wang, Huijun (Frontiers in Cellular Neuroscience, 2018)
Methamphetamine (METH), an extremely and widely abused illicit drug, can cause serious nervous system damage and social problems. Previous research has shown that METH use causes dopaminergic neuron apoptosis and astrocyte-related neuroinflammation. However, the relationship of astrocytes and neurons in METH-induced neurotoxicity remains unclear. We hypothesized that chemokine interleukin (IL)-8 released by astrocytes and C-X-C motif chemokine receptor 1 (CXCR1) in neurons are involved in METH-induced neuronal apoptosis. We tested our hypothesis by examining the changes of CXCR1 in SH-SY5Y cells and in the midbrain and striatum of C57BL/6 mice exposed to METH by western blotting and immunolabeling. We also determined the effects of knocking down CXCR1 expression with small interfering ribonucleic acid (siRNA) on METH-exposed SH-SY5Y cells. Furthermore, we detected the expression levels of IL-8 and the nuclear factor-kappa Β (NF-κΒ) pathway in U87MG cells and then co-cultured the two cell types to determine the role of CXCR1 and IL-8 in neuronal apoptosis. Our results indicated that METH exposure increased CXCR1 expression both in vitro and in vivo, with the effects obtained in vitro being dose-dependent. Silencing of CXCR1 expression with siRNAs reduced the expression of cleaved caspase-3, cleaved poly (ADP-ribose) polymerase, and other related proteins. In addition, IL-8 expression and release were increased in METH-exposed U87MG cells, which is regulated by the NF-κB pathway. Neuronal apoptosis was attenuated by siCXCR1 after METH treatment in the co-cultured cells, which can be reversed after exposure to recombinant IL-8. These results demonstrate that CXCR1 plays an important role in dopaminergic neuronal apoptosis induced by METH and may be a potential target for METH-induced neurotoxicity therapy.